Philosophy and the maternal body : reading silence - Walker, Michelle Boulous, 1959- (Taylor & Francis, 1998)
Philosophy and the Maternal Body is an invaluable study of the crucial significance of the maternal body in philosophy and is essential reading for all those in gender studies, feminist philosophy, psychoanalytic studies and literature.